"Sufficient for the day is its own trouble": Medicalizing Risk and the Way of Jesus - Curlin, Farr A. 1971- (2023)
It is common wisdom that today’s medicine focuses too much on treating those who are sick and too little on preventing the sickness in the first place. This essay proposes that Jesus’ teaching in the Sermon on the Mount challenges that assumption and the preventive medicine to which it has given rise. In light of Jesus’ teaching, the essay identifies four apparent problems with much of preventive medicine. It then offers four heuristics that might form a basic Christian logic for medicalizing risk—for discerning when and why it would be fitting, wise, and faithful for Christians to make use of medicine to avoid future illness and death.